A 3D fully parallel surface-thinning algorithm - Palágyi, Kálmán (Theoretical computer science, 2008)
The thinning is an iterative layer by layer erosion until only the “skeletons” of the objects are left. This paper presents a thinning algorithm for extracting medial surfaces from 3D binary pictures. The strategy which is used is called fully parallel, which means that the same parallel operator is applied at each iteration. An efficient implementation of the proposed algorithm on conventional sequential computers is given and the topological correctness for (26, 6) binary pictures is proved.